Measure Functional Differential Equations in the Space of Functions of Bounded Variation - S. M. Afonso; A. Rontó (Abstract and Applied Analysis)
We establish general conditions for the unique solvability of nonlinear measure functional differential equations in terms of properties of suitable linear majorants.